Beyond Passion and Perseverance: Review and Future Research Initiatives on the Science of Grit - Datu, Jesus Alfonso D. (Frontiers in Psychology, 2021)
Grit, which is originally conceptualized as passion and perseverance for long-term goals, has been associated with optimal performance. Although previous meta-analytic and systematic reviews summarized how grit relates to performance outcomes, they possess considerable shortcomings like: (a) absence of summary on the association of grit with wellbeing outcomes; (b) absence of discussion on mechanisms linking grit to wellbeing; and (c) lack of elaboration on how alternative models can resolve fundamental problems in the grit construct. This integrative review provides a comprehensive summary on the link of grit to performance and wellbeing outcomes. Importantly, it elaborates how alternative models can address flaws in the existing grit theory. Future research directions are discussed on how to move forward the science of grit.